PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN PRODUK TELKOMSEL 4G - Krishna Kusumahadi (Holistik Manajemen: Jurnal Manajemen, 2021)
The development of communication technology is currently growing rapidly, this can be seen from the number of pulses and data packets each year increased. Along with this, the city of Bandung is also listed as a city of communication media users are quite active but penetration of technology changes are not always acceptable in the community The purpose of this study is to examine the magnitude of the effect of Service Quality and Corporate Image on Customer Loyalty. The theory used in this research is the theory of Service Quality, Corporate Image and Customer Loyalty. The research method used in this research is descriptive research method verification, with data analysis techniques using path analysis (path analysis). To determine how big influence of independent variable to dependent variable either partially or simultaneously, then do regression analysis. Meanwhile, to determine whether or not the relationship between independent variables and partially bound, then tested by using the method of correlation partial and Rank Spearman correlation. Furthermore, to test the relationship of research variables simultaneously performed using multiple correlation. Based on the result of research, Quality of Service variable, Corporate Image give influence to Customer Loyalty. This indicates that the Quality of Service and Corporate Image customer's relation can contribute and influence to the creation of loyalty or not from the customer. Keywords: Service Quality, Corporate Image, Customer Loyalty, Telkomsel Card Product Bandung City